Meningkatkan Partisipasi Pemuda dalam Pembangunan Desa Labalimut, Kecamatan Nagawutung, Kabupaten Lembata Melalui Optimalisasi Peran Karang Taruna - Vinsensia Gili Ruron; Agustinus Rewang; Angelika Maria Stellyani; Stephanie Perdana Ayu Lawu; Indriyati Indriyati; Yasinta Palan Peten (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
The lack of youth participation in development activities in Labalimut Village is seen in many aspects, especially regarding development issues within the village. The primary contributing factor to the lack of youth involvement in the development of Labalimut Village is the issue of youth awareness towards the village itself. This study employs field survey research methods with a qualitative approach. Data collected in this study comes from interviews, field notes, personal documents, and supporting official documents. The instruments used in this research include observation, interviews, and documentation. The results of the study indicate that the role of Karang Taruna in the development of Labalimut Village is not active, as evidenced by the lack of activities conducted by KarangTaruna in Labalimut Village and the insufficient synergy between the village government and Karang Taruna in promoting village development.